2018
DOI: 10.1002/jlb.3mir1117-459r
|View full text |Cite
|
Sign up to set email alerts
|

miRNA regulation of innate immunity

Abstract: MicroRNAs (miRNAs) are small noncoding RNA and are pivotal posttranscriptional regulators of both innate and adaptive immunity. They act by regulating the expression of multiple immune genes, thus, are the important elements to the complex immune regulatory network. Deregulated expression of specific miRNAs can lead to potential autoimmunity, immune tolerance, hyper-inflammatory phenotype, and cancer initiation and progression. In this review, we discuss the contributory pathways and mechanisms by which severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 146 publications
2
75
0
Order By: Relevance
“…MicroRNAs are evolutionarily conserved noncoding RNA oligonucleotides and are involved in the pathology of numerous diseases. 26,27 According to previous studies, miR-124, miR-125a, and miR-146b, which are frequently investigated miRNAs, are well known as inflammation-related miRNAs, moreover, they have been identified as direct target genes of lncRNA NEAT1. [18][19][20] Thus, we hypothesized that lncRNA NEAT1 might function via regulating miR-124, miR-125a, and miR-146b in AIS as well.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are evolutionarily conserved noncoding RNA oligonucleotides and are involved in the pathology of numerous diseases. 26,27 According to previous studies, miR-124, miR-125a, and miR-146b, which are frequently investigated miRNAs, are well known as inflammation-related miRNAs, moreover, they have been identified as direct target genes of lncRNA NEAT1. [18][19][20] Thus, we hypothesized that lncRNA NEAT1 might function via regulating miR-124, miR-125a, and miR-146b in AIS as well.…”
Section: Discussionmentioning
confidence: 99%
“…They are expressed by various innate immune cells, such as monocytes, macrophages, DCs, granulocytes, and NK cells. miRNAs are crucial in the development and function of innate immune cells and play a role in adaptive immune cell regulation . Dysfunction of miRNAs can induce inflammatory diseases and autoimmunity .…”
Section: The Role Of the Innate Immune System During The Early Stagesmentioning
confidence: 99%
“…miRNAs are crucial in the development and function of innate immune cells and play a role in adaptive immune cell regulation. 188,189 Dysfunction of miRNAs can induce inflammatory diseases and autoimmunity. 190 In mouse studies, several miRNAs are reported to modulate experimental models of arthritis, including miR- 155, 191 miR-223, 192 and miR-146a.…”
Section: Inhibition Of Myostatin In Vivo Suppressed Lyme Arthritis Inmentioning
confidence: 99%
“…In this case, the effects are due to the intercellular exchange of specific membrane and cargo molecules [7][8][9][10][11][12]. A third mechanism recognized now is due to EVs released from, and then fused to, target cells.…”
Section: Physiological Ev Effects In Immunologymentioning
confidence: 99%
“…When transferred to the cytoplasm of immune target cells these RNAs govern various processes, including expression of immune genes and proteins relevant for development and function [12,14]. When transferred to the cytoplasm of immune target cells these RNAs govern various processes, including expression of immune genes and proteins relevant for development and function [12,14].…”
Section: Physiological Ev Effects In Immunologymentioning
confidence: 99%